Systematic realist synthesis of health-related and lifestyle interventions designed to decrease overweight, obesity and unemployment in adults - Sophia D. Amenyah; Diane Waters; Wen Tang; Lee-Ann Fenge; Jane L. Murphy (BMC, 2022)
Abstract Background Obesity and unemployment are complex social and health issues with underlying causes that are interconnected. While a clear link has been established, there is lack of evidence on the underlying causal pathways and how health-related interventions could reduce obesity and unemployment using a holistic approach. Objectives The aim of this realist synthesis was to identify the common strategies used by health-related interventions to reduce obesity, overweight and unemployment and to determine for whom and under what circumstances these interventions were successful or unsuccessful and why. Methods A realist synthesis approach was used. Systematic literature searches were conducted in Cochrane library, Medline, SocIndex, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, and PsychInfo. The evidence from included studies were synthesised into Context-Mechanism-Outcome configurations (CMOcs) to better understand when and how programmes work, for which participants and to refine the final programme theory. Results A total of 83 articles met the inclusion criteria. 8 CMOcs elucidating the contexts of the health-related interventions, underlying mechanisms and outcomes were identified. Interventions that were tailored to the target population using multiple strategies, addressing different aspects of individual and external environments led to positive outcomes for reemployment and reduction of obesity. Conclusion This realist synthesis presents a broad array of contexts, mechanisms underlying the success of health-related interventions to reduce obesity and unemployment. It provides novel insights and key factors that influence the success of such interventions and highlights a need for participatory and holistic approaches to maximise the effectiveness of programmes designed to reduce obesity and unemployment. Trial registration PROSPERO 2020 CRD42020219897 .